2020
DOI: 10.1097/prs.0000000000006902
|View full text |Cite
|
Sign up to set email alerts
|

Keeping the Finger on the Pulse: Cardiac Arrhythmias in Hand Surgery Using Local Anesthesia with Adrenaline

Abstract: Background: The wide-awake local anesthesia no tourniquet (WALANT) technique in hand surgery is gaining popularity. The authors aimed to prospectively analyze the frequency and type of arrhythmias in patients undergoing hand surgery under local anesthesia and to examine whether the addition of adrenaline affects their incidence. Methods: Adult patients undergoing hand surgery under local anesthesia were randomized into two groups: group 1, local anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…Procedure rooms are less expensive and more efficient. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 The savings begin before the patient steps foot in the procedure room, with no need for preoperative laboratory testing and medical evaluations. In a study of preoperative carpal tunnel patients, Greenfield et al 8 found a per-patient average cost of $858.74 was spent on preoperative work-ups and nonsurgical management of patients who underwent carpal tunnel release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedure rooms are less expensive and more efficient. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 The savings begin before the patient steps foot in the procedure room, with no need for preoperative laboratory testing and medical evaluations. In a study of preoperative carpal tunnel patients, Greenfield et al 8 found a per-patient average cost of $858.74 was spent on preoperative work-ups and nonsurgical management of patients who underwent carpal tunnel release.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Additionally, there are cost savings associated with the decreased need for surgical drapes, equipment, and hospital staffing. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 There is also a decrease in the waste generated by these procedures, as they are typically done under minor field sterility, which consists of sterile prep, a single drape, a minor instrument tray, sterile gloves and a mask (no gown or antibiotics), and local anesthesia. 16 , 29 …”
mentioning
confidence: 99%
“…Farkash et al monitored heart rhythms during hand procedures under WALANT and did not find any arrhythmogenic properties associated with the local anesthesia used. They concluded that heart monitoring is not needed during these procedures in patients who have no history of arrhythmias [47]. Another potential risk of using epinephrine during WALANT is digital ischemia.…”
Section: Use Of Local Anesthesiamentioning
confidence: 99%
“…Farkash und Mitarb. untersuchten in einer aktuellen Studie 102 handchirurgische, in Lokalanästhesie operierte Patienten bezüglich des Auftretens von Arrhythmien 13 . Die Patienten wurden in 2 Gruppen randomisiert.…”
Section: Diskussionunclassified